Integrated metagenomics and targeted-metabolomics analysis of the effects of phenylalanine on loperamide-induced constipation in rats - Yang, Chuanli; Bai, Xinshu; Hu, Tianjiao; Xue, Xin; Su, Xiaohu; Zhang, Xuan; Wu, Teng; Zhang, Mingxia; Shen, Xiaobing; Dong, Xiushan (Frontiers in Microbiology, 2022)
Functional constipation is a common functional gastrointestinal disease. In our previous study, we found that the gut microbiota structure was disordered and the level of phenylalanine (Phe) in serum was decreased in constipated women. We conducted the present study to elucidate the role of Phe in remodeling the composition of gut microbiota and the relationship between gut microbiota and serum metabolites. Here, we demonstrated that Phe treatment significantly enhanced intestinal motility, suppressed inflammatory responses, and prevented intestinal barrier damage in rats with loperamide (Lop)-induced constipation. By metagenomic sequencing, the disbalanced gut microbial profile was analyzed in constipated rats. Phe treatment reversed changes in the abundance of several gut bacteria at the phylum, genus, and species levels. Further, we observed distinct metabolic patterns in constipated rats through targeted metabolomics and identified constipation-related gut microbial species linked to changes in circulating neurotransmitter metabolites. The abundances of species s_Lactobacillus murinus, s_Enterococcus italicus, s_Lactobacillus animalis, s_Lactobacillus apodemi, s_Enterococcus faecalis, and s_Lactobacillus backii were positively correlated with L-asparagine, L-Glutamic acid, Putrescine, and Spermidine levels. The abundances of s_Lactobacillus johnsonii and s_Butyricimonas virosa were negatively correlated with L-asparagine, L-Glutamic acid, Putrescine, and Spermidine levels. Taken together, our findings suggest that Phe can ameliorate the development of Lop-induced constipation in rats by remodeling the gut microbial community structure and changing metabolite levels.